Keputusan Pemilihan Formula Sabun Menggunakan Analytical Hierarchy Process - Purwani, Annie; Astuti, Amalia Yuli; Wahyuningsih, Titi; Ghozali, Muhammad Nizar (OPSI, 2023)
Waste cooking oil is one of household waste. Waste cooking oil is usually disposed to the sewers or gardens. Utilization of waste cooking oil is by recycling it into a solid soap product. The production of solid soap from waste cooking oil is a solution to reduce waste. There are various formulas for making soap products from waste cooking oil. In order to utilize waste cooking oil becomes maximal dan useful, it is necessary to select the best formula for further development. The research begins by identifying the soap formula with a simple process. The identification results obtained six soap formulas that can be produced on a household scale. The six soap formulas were then produced and tested according to Indonesia’s national standards (SNI). The method used to select the best formula was Analytical Hierarchy Process (AHP), which involved four partisipants as experts. The result of the decision of the best soap formula is Soap 6. Meanwhile, the three priority attributes for decision-making are soap standard (SNI), cleaning power, and the ability to hold bacteria.